Type-1.5 Diabetes Mellitus with Autoimmune Hypothyroidism: A Rare Combination - UG Thakkar; AV Vanikar; HL Trivedi (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2016)
Autoimmune hypothyroidism may associate with type-1 Diabetes mellitus (DM) is a well-known entity as polyglandular autoimmune syndrome type-3. Type-1.5 DM is also known as late onset autoimmune mediated diabetes mellitus of adulthood (LADA) describing as- patients with type-2 diabetic phenotype based on age, not etiology combined with islet-cell antibodies and progressive β-cell failure, requiring life-time insulin therapy. Authors report a misdiagnosed type-2 diabetic since 3-years, of 35-years-male with known case of hypothyroidism had uncontrolled hyperglycemia, 12.7% glycosylated hemoglobin (HbA1C), 1.09ng/ml serum C-peptide and 26IU/ml glutamic acid decarboxylase (GAD) antibody, with anti-microsomal antibody titre of 827IU/ml and anti-thyroglobulin antibody titre of 130IU/ml, on  3 oral hypoglycemic agents. He was diagnosed as type-1.5 DM with autoimmune hypothyroidism. During 11-months of follow-up, after initiating insulin therapy patient had 6.7% HbA1C and normal thyroid function with oral thyroxin medication. So all young diabetic adults should evaluate for type-1.5 DM with autoimmune hypothyroidism.